Penerapan Platform Fishtech Alat Monitoring dan Kontrol Otomatis Berbasis IoT untuk Budidaya Udang di Lamongan - Indra Gunawan, Agus; Afiful Maula, Ricky; Harun Al Rasyid, M. Udin; Rifa’i, Ahmad (Journal of Applied Community Engagement, 2022)
Indonesia is an archipelagic country which has enormous potential in terms of fishery productivity. One type of fishery productivity in Indonesia is shrimp farming productivity. However, despite having high potential, not a few cultivators experience crop failure. This is due to several factors, including the lack of understanding of the cultivators who do not observe the important parameters of the pond, cultivation methods based on hereditary techniques that do not see the real condition of the pond, and so on. Therefore, to overcome these problems, this community service program aims to implement a technology utilization for monitoring, management and automatic control so that aquaculture ponds are always in optimal condition. This system is called the fishtech platform which implements Internet of Things technology. With Internet of Things (IoT) technology, it is possible for users (cultivators) to know in real time the condition and quality of aquaculture ponds.